Outlaw the true story of Claude Dallas - Long, Jeff (New York William Morrow and Company, Inc., 1985)
Today's West-honor-bound, tradition-bound. It still has a language and a code of ethics all its own, even as it is being corralled by barbed wire, federal legislation, and complex machinery. Claude Dallas and Bill Pogue were two extraordinary men who lived in the West of today but were ruled by the ideals of the previous century. Joined together by the land, diametrically opposed in faith, they were bound to clash in battle. Claude Dallas, buckaroo and poacher, lived off the land, killing what he needed to eat, pitching camp where the countryside was most hospitable. Bill Pogue, fish and game warden, was a naturalist, a loner, and a fierce protector of the law. On January 5, 1981, Bill Pogue entered Dallas's camp accompanied by fellow game warden Conley Elms in order to check Dallas's traps. He left the camp in the back of Dallas's truck, dead, two bullets in his chest, one in his head. Elms's body was found floating in the Owyhee River.
Keywords: Dallas, Claude; Criminals -- Idaho -- Biography; Murder -- Idaho -- Case studies; Trials (Murder) -- Idaho -- Case studies